Assessment of nutritional status by composite index for anthropometric failure: A study among slum children in Bankura, West Bengal - Subhadeep Shit; Pranita Taraphdar; Dipta K Mukhopadhyay; Apurba Sinhababu; Akhil B Biswas (Wolters Kluwer Medknow Publications, 2012)
A community-based cross-sectional study was conducted to find out the prevalence of composite index of anthropometric failure (CIAF) among 117 slum dwelling under-five children in Bankura town, West Bengal and its relation with some common socio-economic factors. Among study population, the prevalence of underweight was 41.6%, whereas CIAF was 80.3%. CIAF gave a near complete estimation of undernutrition unlike underweight. Children who were unimmunized, with more number of siblings, living in a nuclear family, or with illiterate mothers were more likely to be undernourished.